Draft Genome Assembly of Neisseria lactamica Type Strain A7515 - Minogue, T. D. (American Society for Microbiology, 2014)
We present the scaffolded genome assembly of Neisseria lactamica type strain A7515 (ATCC 23970) as submitted to NCBI under accession no. JOVI00000000. This type strain of the lactose-fermenting Neisseria species is often used in quality control testing and intra-genus phylogenetic analyses. The assembly includes four contigs placed into a single scaffold.